Scene Text Analysis in Unconstrained Environment using Deep Networks - Bagi, Randheer (IIT(BHU) Varanasi, 2020)
Abstract is available in content.
Keywords: Scene Text Analysis in; Unconstrained Environment; using Deep Networks